Physico-Chimie Et Teneurs Metalliques Des Eaux De L’estuaire De L’oued Sebou Durant Des Annees De Dragage Du Sable/ 2007, 2014, 2015, 2016 - Izougarhane, Mohammed; Mansouri, Dalale; El Ibaoui1Hamid; Chakiri, Said; Fadli, Mohamed (European Scientific Journal, ESJ, 2016)
This work focuses on the physical, chemical and metal characterization of the estuary waters of Oued Sebou during a long period of sand dredging. To do this, several physicochemical parameters were evaluated during periods 2007 and 2014-2016. The results showed that this estuary has a significant degree of pollution. The source of this pollution is diverse: urban waste, industrial waste, agricultural activities. This pollution is accentuated by the action of repeated dredging that increases the turbidity and the suspended solids content which covers the seabed during immersions that are covering the sediment and disturbs the physicochemical equilibrium of the estuary. So, indirectly this operation of dredging influences the parameters that are related to the amount and quality of materials suspended such as the dissolved oxygen content and orthophosphates and the brightness level in the water and over up the sediment.Indeed, for the majority of the physicochemical parameters assessed, the water of the estuary was belonging to a middle class, poor class or very poor class. Thus, the operation of dredging should consider the ecological balance of the coastal zone. Note also that the contents of assessed heavy metals are not worrisome. However, their risks might be amplified by the dredging operations.